Synthesis of Sago Hampas Activated Carbon Aerogel (SHACA) for sago wastewater (SWW) treatment - Madelin, Demong (Universiti Malaysia Sarawak, 2019)
Sago hampas is well known with its special component in treating waste water effluent. An alternative was made on this raw material to transform sago hampas into activated carbon Aerogel. Aerogel can be produced from a wide range of raw materials of agricultural origin and it has a wide of usage, which includes as an adsorbent that act as medium in adsorbing organic pollutant content in waste water. These technologies can reduce the waste especially produced from the agricultural activities such as straws, bagasse, pith, and others. Apart from that, a low-cost and eco-friendly product can be generated, hence, minimizes the hazardous. Activated carbon Aerogel is found to be highly effective product to remove organic pollutants. Two techniques of drying were used which are pyrolysis and freeze-drying that give different properties in the activated carbon aerogel from sago hampas analysed by FTIR, FESEM, BET and particle size analyser (PSA). Samples were used to treat sago wastewater (SWW). There are three types of organic pollutant that is remove from the SWW and measurements were taken in terms of Chemical Oxygen Demand (COD), turbidity and Total Suspended Solid (TSS). The findings prove that freeze-drying give the best the Aerogel adsorbent that removed pollutants up to 80%. Meanwhile, the product from pyrolysis has less performance in the of pollutants. Results shows also showed that the higher the dosage of aerogel used, the more efficient the removal performance. However, tested for smaller particle size of adsorbent showed lower performance compared to those observed for particle sizes at 1.5 cm and 1mm. Outcomes of this wor indicates the potential of converting sago hampas become aerogel for wastewater treatment.